God and moral law : on the theistic explanation of morality - Murphy, Mark C (Oxford ; New York : Oxford University Press, 2011)
"Does God's existence make a difference to how we explain morality? Mark C. Murphy critiques the two dominant theistic accounts of morality--natural law theory and divine command theory--and presents a novel third view. He argues that we can value natural facts about humans and their good, while keeping God at the centre of our moral explanations. The characteristic methodology of theistic ethics is to proceed by asking whether there are features of moral norms that can be adequately explained only if we hold that such norms have some sort of theistic foundation. But this methodology, fruitful as it has been, is one-sided. God and Moral Law proceeds not from the side of the moral norms, so to speak, but from the God side of things: what sort of explanatory relationship should we expect between God and moral norms given the existence of the God of orthodox theism? Mark C. Murphy asks whether the conception of God in orthodox theism as an absolutely perfect being militates in favor of a particular view of the explanation of morality by appeal to theistic facts. He puts this methodology to work and shows that, surprisingly, natural law theory and divine command theory fail to offer the sort of explanation of morality that we would expect given the existence of the God of orthodox theism. Drawing on the discussion of a structurally similar problem--that of the relationship between God and the laws of nature--Murphy articulates his new account of the relationship between God and morality, one in which facts about God and facts about nature cooperate in the explanation of moral law."--Publisher's website
"Does God's existence make a difference to how we explain morality? Mark C. Murphy critiques the two dominant theistic accounts of morality--natural law theory and divine command theory--and presents a novel third view. He argues that we can value natural facts about humans and their good, while keeping God at the centre of our moral explanations. The characteristic methodology of theistic ethics is to proceed by asking whether there are features of moral norms that can be adequately explained only if we hold that such norms have some sort of theistic foundation. But this methodology, fruitful as it has been, is one-sided. God and Moral Law proceeds not from the side of the moral norms, so to speak, but from the God side of things: what sort of explanatory relationship should we expect between God and moral norms given the existence of the God of orthodox theism? Mark C. Murphy asks whether the conception of God in orthodox theism as an absolutely perfect being militates in favor of a particular view of the explanation of morality by appeal to theistic facts. He puts this methodology to work and shows that, surprisingly, natural law theory and divine command theory fail to offer the sort of explanation of morality that we would expect given the existence of the God of orthodox theism. Drawing on the discussion of a structurally similar problem--that of the relationship between God and the laws of nature--Murphy articulates his new account of the relationship between God and morality, one in which facts about God and facts about nature cooperate in the explanation of moral law."--Publisher's website
Introduction: God and morality -- Moral law -- Theistic explanation of moral law -- Natural law theory -- Theological voluntarism -- Theistic explanation of the laws of nature -- Moral concurrentism
Includes bibliographical references (p. [181]-187) and index
Keywords: Christian ethics; Natural law -- Religious aspects -- Christianity; Divine commands (Ethics)